스마트폰을 활용한 UAM 항적정보 구현 - 이승준; Seungjun Lee; 홍승범; Seungpum Hong; 김도현; Dohyun Kim; 장효석; Hyoseok Chang (한국항행학회논문지, 2025)
다수의 비행체가 도심 하늘에서 자유롭고 단절 없이(seamless) 비행할 수 있는 안전하고 효율적인 공역 관리 지원이 필수적이다. 기존 항공교통관리의 인력 중심 관제 시스템으로는 복잡한 UAM 운용환경을 관리하는 데는 한계가 있어 첨단 정보처리 기반 교통관리체계가 필요하다. 본 연구에서는 스마트폰을 활용한 UAM 항적 감시 및 추적을 위한 기술을 제시하고, 실증분석을 통해 오차 범위 등을 확인하여 실용 가능성에 대해 제시하고자 한다. 위치 정확도 향상, 보안성 문제 등 아직 개선 보완되어야 할 부분이 있지만, 향후 효율적인 UAM 교통관리에 이바지하기를 기대한다. Safe and efficient airspace management support is essential to enable multiple aircraft to fly freely and seamlessly in urban areas. The existing human-centered air traffic management control system has limitations in managing the complex UAM operation environment, so an advanced information processing-based traffic management system is required. In this study, a technology for UAM flight monitoring and tracking using smartphones was developed, and the practical feasibility was presented by confirming the error range and other factors through empirical analysis. Although there are still improvements to be made, such as improved location accuracy and security issues, it is expected to contribute to efficient UAM traffic management in the near future.